2016
DOI: 10.1186/s13041-016-0192-8
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in parvalbumin expression not loss of the parvalbumin-expressing GABA interneuron subpopulation in genetic parvalbumin and shank mouse models of autism

Abstract: BackgroundA reduction of the number of parvalbumin (PV)-immunoreactive (PV+) GABAergic interneurons or a decrease in PV immunoreactivity was reported in several mouse models of autism spectrum disorders (ASD). This includes Shank mutant mice, with SHANK being one of the most important gene families mutated in human ASD. Similar findings were obtained in heterozygous (PV+/-) mice for the Pvalb gene, which display a robust ASD-like phenotype. Here, we addressed the question whether the observed reduction in PV i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
182
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 200 publications
(222 citation statements)
references
References 106 publications
29
182
2
Order By: Relevance
“…Within the pool of VVA + cells, ∼70% and ∼65% of cells in control mice were also identified as PV + in the striatum ( Figure 2A ) and the cortex ( Figures 3A and 4A ), respectively. Similar values were obtained in previous studies (Ye and Miao, 2013; Filice et al, 2016). The number of PV + cells in the striatum of VPA mice was reduced by ∼15% ( p = 0.0093) compared to controls ( Figure 2A ).…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Within the pool of VVA + cells, ∼70% and ∼65% of cells in control mice were also identified as PV + in the striatum ( Figure 2A ) and the cortex ( Figures 3A and 4A ), respectively. Similar values were obtained in previous studies (Ye and Miao, 2013; Filice et al, 2016). The number of PV + cells in the striatum of VPA mice was reduced by ∼15% ( p = 0.0093) compared to controls ( Figure 2A ).…”
Section: Resultssupporting
confidence: 92%
“…Therefore, in addition to counting PV + cells via anti-PV immunostaining, we simultaneously quantified the number of Vicia Villosa Agglutinin VVA + cells, i.e., neurons surrounded by PNNs in the same brain regions to obtain an alternative estimate for the number of Pvalb cells. VVA is a lectin that binds to N -acetylgalactosamine residues of PNNs, which specifically surround Pvalb neurons (Hartig et al, 1992; Haunso et al, 2000), as also shown in our previous study (Filice et al, 2016). VVA + cells were considered to serve as a correlate for Pvalb neurons; a typical example of PV and VVA co-localization is shown in Figure 1 .…”
Section: Resultssupporting
confidence: 76%
See 3 more Smart Citations